Assembly of an R3N52- chain by cycloaddition of a hydrazinediide and an azide at zirconium and its thermal fragmentation - Gehrmann, Thorsten; Lloret Fillol, Julio; Wadepohl, Hubert; Gade, Lutz H. (Angewandte Chemie. International edition, 2009)
Breaking the chain: Reaction of a zirconium hydrazinediide with organoazides gives 2-pentazene-1,4-diyl complexes, such as [Zr(N2TBSNpy)N(Ad)N3NPh2] (C gray, N blue, Si green, Zr turquoise), by formal [2+3] cycloaddition. Bonding within the N5 chain is investigated using density functional calculations. These complexes thermally eject N2 to give side-on bonded diazenides.
Gesehen am 15.12.2022
Im Titel ist die Zahl 2 und das Zeichen - hochgestellt und die Zahlen 3 und 5 sind tiefgestellt